STRATEGI PEMASARAN KRECEK KULIT KERBAU DI UD.SUMBER BAROKAH KECAMATAN BANYUDONO KABUPATEN BOYOLALI - M.Th.Handayani M.Th.Handayani; Egydia Narera Damayanti; Kusriani Prasetyowati (JURNAL ILMIAH AGRINECA, 2018)
The objective of this research were to : (1) analyze the internal and external factors which can be applied to marketing of krecek buffalo in UD. Sumber Barokah Banyudono Subdistrict Boyolali Regency; (2) formulate alternative strategic which can be applied to marketing of krecek buffalo in UD. Sumber Barokah Banyudono Subdistrict Boyolali Regency; (3) determine the strategic priorities which can be applied to marketing of krecek buffalo in UD. Sumber Barokah Banyudono Subdistrict Boyolali Regency. The basic method of this research is used analytical descriptive. Determinate location of the research was conducted by purposive sampling in Banyudono Village, Banyudono Subdistrict, Boyolali Regency. The data souece used primary data and secondary data. Method of data analysis used (1)SWOT analysis to identifity internal and external factors are strength, weakness, opportunities, and threaths; (2) SWOT matrix to formulate an alternative product marketing strategy; (3) QSPM to determinate priority product marketing strategy. The research result relevated that strategies can be apllied in marketing of strategic krecek buffalo in Ud. SumberBarokah based on the QSPM analysis namely to create and operate the production process in accordance with operational standars procedures by maximizing human resourse to make product more innovative and quality.